Mirror symmetry and Fano manifolds - Coates, Tom; Corti, Alessio; Galkin, Sergey; Golyshev, Vasily; Kasprzyk, Alexander M. (European Mathematical Society, 2013)
We consider mirror symmetry for Fano manifolds, and describe how one can recover the classification of 3-dimensional Fano manifolds from the study of their mirrors. We sketch a program to classify 4-dimensional Fano manifolds using these ideas.